Slater to Mott Crossover in the Metal to Insulator Transition of Nd2⁢Ir2⁢O7 - Nakayama, M. (2016)
We present an angle-resolved photoemission study of the electronic structure of the three-dimensional pyrochlore iridate Nd2⁢Ir2⁢O7 through its magnetic metal-insulator transition. Our data reveal that metallic Nd2⁢Ir2⁢O7 has a quadratic band, touching the Fermi level at the Γ point, similar to that of Pr2⁡Ir2⁢O7. The Fermi node state is, therefore, a common feature of the metallic phase of the pyrochlore iridates. Upon cooling below the transition temperature, this compound exhibits a gap opening with an energy shift of quasiparticle peaks like a band gap insulator. The quasiparticle peaks are strongly suppressed, however, with further decrease of temperature, and eventually vanish at the lowest temperature, leaving a nondispersive flat band lacking long-lived electrons. We thereby identify a remarkable crossover from Slater to Mott insulators with decreasing temperature. These observations explain the puzzling absence of Weyl points in this material, despite its proximity to the zero temperature metal-insulator transition.